2015
DOI: 10.1002/biot.201400602
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a branch of the UDP‐precursor biosynthesis pathway enhances the production of capsular polysaccharide in Escherichia coli O5:K4:H4

Abstract: Escherichia coli K4 produces a capsule with a chemical structure that resembles chondroitin, a molecule with established chondro protective properties. The endogenous genes pgm and galU are involved in the biosynthesis of UDP-glucose which is a critical intermediate in carbohydrate metabolism and biochemical precursor of UDP-glucuronic acid. Together with UDP-N-acetylgalactosamine, UDP-glucuronic acid is used as sugar donor for capsule biosynthesis. The aim of the study was to evaluate how a change in the path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 24 publications
(32 reference statements)
1
28
0
Order By: Relevance
“…Among these, UDP-Glu, the precursor of UDP-GlcA, is obtained by the sequential conversion of Glc-6P to glucose-1-phosphate (Glc-1P), and further into UDP-Glu, by the concerted action of a phosphoglucomutase (Pgm), and of a pyrophosphorylase (GalU). We previously demonstrated that higher concentrations of Pgm and GalU significantly influenced polysaccharide production and UDP-sugar pools in a recombinant E. coli K4 strain also overexpressing a positive regulator of the CPS operon (Cimini et al, 2015). During the exponential phase, higher titers of both UDP-Glu and UDP-GlcA, and an unexpected reduction of UDP-GlcNAc and UDP-GalNAc pools were observed combined to a significant increase of CPS (Cimini et al, 2015).…”
Section: Introductionmentioning
confidence: 95%
“…Among these, UDP-Glu, the precursor of UDP-GlcA, is obtained by the sequential conversion of Glc-6P to glucose-1-phosphate (Glc-1P), and further into UDP-Glu, by the concerted action of a phosphoglucomutase (Pgm), and of a pyrophosphorylase (GalU). We previously demonstrated that higher concentrations of Pgm and GalU significantly influenced polysaccharide production and UDP-sugar pools in a recombinant E. coli K4 strain also overexpressing a positive regulator of the CPS operon (Cimini et al, 2015). During the exponential phase, higher titers of both UDP-Glu and UDP-GlcA, and an unexpected reduction of UDP-GlcNAc and UDP-GalNAc pools were observed combined to a significant increase of CPS (Cimini et al, 2015).…”
Section: Introductionmentioning
confidence: 95%
“…In this article, we focus on getting a step closer to preparing CS from simple sugars like glucose in an Escherichia coli cell‐based system. Previous reports show that chondroitin can be produced using E. coli K4 and engineered BL21 strains . Other reports also show successful expression of active sulfotransferase enzymes in E. coli .…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of chondroitin polymerase suggested a higher binding affinity for UDP-GalNAc (Zanfardino et al 2010) and, a simulated implementation of the UDP-GalNAc productive branch by glutamine addition boosted capsular polysaccharide production in recombinant E. coli K4 (Cimini et al 2015). However, in the present work addition of GalNAc only resulted in a slight reduction of HA titers, leaving the production of chondroitin unchanged and a higher (80%) concentration of the latter inside the cells compared to that found in control conditions.…”
Section: Discussionmentioning
confidence: 99%
“…K4 and K5 polysaccharides are consolidated precursors of chondroitin and heparin; however, CS is still obtained from limited and potentially harmful, animal sources such as chicken keel, shark fins, and swine or bovine trachea. Several efforts have been made to use E. coli K4, or its biosynthetic machinery in a different background, to generate cell factories for the production of chondroitin, and encouraging results were obtained (Cimini et al 2013, 2015; He et al 2015; Jin et al 2016). The reason lies in the fact that the capsular polysaccharide of this uropathogenic strain, composed of alternating residues of N -acetylgalactosamine (GalNAc) and glucuronic acid (GlcA), has a structure that closely resembles the backbone of CS.…”
Section: Introductionmentioning
confidence: 99%